Economic opportunities for communities through community-based tourism in Huamuang Subdistrict community, Muang Pan, Lampang Thailand. - Wongwirach, Kajohnsak; Janasak, Siraya; Mookam, Thanaphon; Luanyai, Natedao (Area Based Development Research Journal, 2024)
The community of Hua Mueang Subdistrict, Mueang Pan District, Lampang Province of Thailand, is a pilot area for a poverty alleviation model that utilizes community capital. The target group of impoverished individuals in Ban Rai Village, Moo 4, participated in the 5 following stages. The first stage was to analyze the community’s spatial context that can promote tourism through self-assessment by the community and setting guidelines for tourism development. Secondly, community resources were linked with economic opportunities and addressing poverty by setting poverty alleviation goals alongside creating economic opportunities within the community, designing areas for development, and creating economic opportunities through tourism. The community capital utilized includes natural capital, such as the Mae Soi River, which has been developed into a tourist attraction with bamboo pavilions and walkways, and social capital, such as the lifestyle of ethnic groups and local people, as well as traditional knowledge of preparing food from the forest and river. The third stage was creating tangible outcomes through local preparedness, raising awareness at the village level, and creating an operational plan. The next stage Involved network partners to enhance spatial potential, focusing on developing tourist attractions and local food. Finally, driving activities through community participation included managing community-based tourism, presenting tourist attractions to the public, and creating economic opportunities for the community. As a consequence, the community now offers tourist attractions and activities, such as river tubing at Mae Soi, raising the number of visitors. The community generates income from selling local products, providing services, and employing people to construct bamboo pavilions, prepare food, provide services to tourists, and sell goods within the community. The process has led to economic circulation and opportunity creation within the community, the establishment of tourism management systems, community welfare development, learning promotion, occupational development, and the establishment of a market for community products. effectively addressing poverty through both immediate and sustainable solutions.